1992
DOI: 10.1177/000992289203100202
|View full text |Cite
|
Sign up to set email alerts
|

Needle Aspiration of Neck Abscesses In Children

Abstract: Needle aspiration of neck abscesses with CT-scan guidance was studied in 17 children with 18 abscesses from 1986 to 1991. Clinical and radiologic findings were analyzed according to treatment outcome. A majority of abscesses (55.6%) resolved after treatment with one to two attempts at needle aspiration and parenteral antibiotics. Unilocular abscesses were more likely than multilocular abscesses to resolve with needle aspiration. In general, abscesses in younger children who presented with smaller neck masses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 7 publications
0
16
1
3
Order By: Relevance
“…There are several reports of closed surgical drainage of head and neck abscesses [23][24][25][26][27]. Ultrasound and CT scanning guidance were the most common techniques used for placement of needles or indwelling catheters in these abscesses.…”
Section: Retropharyngeal and Parapharygeal Abscessesmentioning
confidence: 99%
“…There are several reports of closed surgical drainage of head and neck abscesses [23][24][25][26][27]. Ultrasound and CT scanning guidance were the most common techniques used for placement of needles or indwelling catheters in these abscesses.…”
Section: Retropharyngeal and Parapharygeal Abscessesmentioning
confidence: 99%
“…The morbidity associated with open surgical drainage has led to the consideration of conservative management via needle (18-20-gauge) aspiration or catheter drainage under CT or sonographic guidance. [5][6][7] We report 2 cases of successful nonsurgical management of a thyroid abscess with percutaneous 21-gauge needle aspiration. In both cases, the procedure was performed under sonographic guidance using an SSA-240A scanner (Toshiba Medical Systems, Tokyo, Japan) equipped with an SM-708A 7.5-MHz mechanical sector transducer.…”
mentioning
confidence: 99%
“…Poe et al in 1996 reported the successful CT guided aspiration of deep neck abscesses in four patients. Brodsky et al [34] has recommended needle aspiration in children with small superficial neck abscess. We found very disappointing results with blind aspiration and empirical therapy.…”
Section: Treatment Optionsmentioning
confidence: 99%